Honest broker? : the national security advisor and presidential decision making - Burke, John P (Joseph V. Hughes Jr. and Holly O. Hughes Series on the Presidency and Leadership, 2009)
“Quis custodiet ipsos custodes?” “Who will be guarding the guardians?”—Juvenal The U.S. president’s decisions on national security and foreign policy reverberate around the world. The National Security Council (NSC) and the national security advisor are central to the decision making process. But how was the role of the national security advisor originally understood, and how has that understanding changed over time? Above all, how has the changing role of the national security advisor affected executive decisions and the implementation of policy? Now, presidential scholar John P. Burke systematically and thoroughly addresses these questions. In Honest Broker?, he reviews the office of national security advisor from its inception during the Eisenhower presidency to its latest iteration in the White House of George W. Bush. He explores the ways in which the original conception of the national security advisor—as an “honest broker” who, rather than directly advocate for any certain policy direction, was instead charged with overseeing the fairness, completeness, and accuracy of the policymaking process—has evolved over time. In six case studies he then analyzes the implications of certain pivotal changes in the advisor’s role, providing thoughtful and sometimes critical reflections on how these changes square with the role of “honest broker.” Finally, Burke offers some prescriptive consideration of how the definition of the national security advisor’s role relates to effective presidential decision making and the crucial issues of American national security. Honest Broker? will be an important resource for scholars, students, political leaders, and general readers interested in the U.S. presidency, foreign policy, and national security